1204. Catheter-Associated Urinary Tract Infections (CAUTIs) and Secondary Hospital-Onset Bloodstream Infections (HO-BSIs)… Only the Tip of the Iceberg?. (15th December 2022) - Ai, ChinEn; Jung, Molly; Kelly, Timothy; Yu, Kalvin
Abstract: Background: HO-BSIs – secondary to urinary tract infections (UTIs) – can result in substantial morbidity and mortality. The Centers for Disease Control and Prevention report that CAUTIs are the leading cause of secondary BSIs. However, more than 70% of hospital-onset UTIs (HO-UTIs) may be non-device associated. If that is the case, are a substantial number of HO-BSIs caused by non-CAUTI HO-UTIs? Methods: A retrospective cohort analysis of nosocomial infections from 37 US hospitals was conducted using de-identified, real-world data from an electronic infection surveillance system. The analytic cohort included adults ≥ 18 years, without an infection diagnosis, and hospital length of stay ≥ 2 days, between October 2015 and June 2019. HO-UTI subjects presented with a non-contaminated positive urine culture on day 3 or later. Clinically meaningful HO-UTIs, were those with antimicrobials ordered ±2 days of the positive urine culture. CAUTI was defined per the National Healthcare Safety Network definition. Non-CAUTI HO-UTI were HO-UTIs not meeting the CAUTI definition. Secondary HO-BSIs were defined as non-contaminated, positive blood cultures occurring 2 days before or 4 days after the positive urine specimen, requiring an antimicrobial susceptibility test, and presenting with the same pathogen. Results: Of the 568, 293 inpatient admissions, 465, 246 met the inclusion criteria. The vast majority of CAUTIs (401 of 436; 92%) and 75% of non-CAUTI HO-UTIs (3, 256 of 4, 374) were clinically meaningful. The relative burden of secondary HO-BSI was greater in patients with CAUTI (8%) compared to non-CAUTI HO-UTI (3%). However, the absolute risk of secondary HO-BSI was 3-times greater in non-CAUTI HO-UTI compared to CAUTI (96 cases vs 32 cases, respectively). 56% of secondary HO-BSI in CAUTI, and only 31% of secondary HO-BSI in non-CAUTI HO-UTI, likely originated in the intensive care unit (ICU). Case Tree Frequency of CAUTI and non-CAUTI HO-UTI. Frequency of secondary HO-BSI. Location of HO-UTI. Conclusion: This retrospective, observational study found clinically meaningful non-CAUTI HO-UTIs to be 10-fold higher than the number of CAUTIs. In addition, the absolute burden of secondary HO-BSI is substantially higher in these non-CAUTI HO-UTIs and more likely to be associated with the non-ICU setting. The data suggests that evaluating CAUTI alone may underestimate the true burden of clinically meaningful HO-UTI. Disclosures: ChinEn Ai, MPH, BD - Becton, Dickinson and Company: Employee|BD - Becton, Dickinson and Company: Stocks/Bonds Molly Jung, MPH, BD - Becton, Dickinson and Company: Employee|BD - Becton, Dickinson and Company: Stocks/Bonds Timothy Kelly, MS, MBA, BD - Becton, Dickinson and Company: Employee|BD - Becton, Dickinson and Company: Stocks/Bonds Kalvin Yu, MD, FIDSA, Becton, Dickinson and Company: Employee of, and shareholder in, Becton, Dickinson and Company, and the company received funding from GlaxoSmithKline plc. to conduct this study|GlaxoSmithKline plc.: GlaxoSmithKline plc.-sponsored study 212502.